Genotyping of Aspergillus fumigatus in Formalin-Fixed Paraffin-Embedded Tissues and Serum Samples From Patients With Invasive Aspergillosis - Theun de Groot; Ferry Hagen; Ferry Hagen; Willem Vreuls; Paul E. Verweij; Paul E. Verweij; Anuradha Chowdhary; Jacques F. Meis; Jacques F. Meis; Jacques F. Meis (Frontiers in Cellular and Infection Microbiology, 2018)
Invasive aspergillosis (IA) is a deep tissue infection with a high mortality occurring mostly in immunocompromised patients. To investigate the pathology of patients with IA it may be important to determine the genotype of the invasive isolate of Aspergillus, however available tissues for study are often formalin fixed paraffin embedded (FFPE). Although DNA has been successfully isolated from such tissues for species identification, genotyping of Aspergillus species on such tissues has not yet been performed. In this study we aimed to determine the genotype of Aspergillus fumigatus in FFPE tissue and serum samples from five patients with invasive aspergillosis using nine highly polymorphic short tandem repeat (STRAf) loci. FFPE lung and bronchial biopsies from all patients were successfully typed. By comparing the latter result with non-FFPE materials from non-sterile samples such as sputum, bronchoalveolar lavage and lung abscess, we found identical genotypes within three patients, while the two other patients had a dominant genotype shared among all sample types. Genotyping of serum samples was successful in two serum samples with galactomannan ratios of 4 and 5.6, but failed in serum samples with galactomannan levels <0.5. In addition, testing a subset of these materials with the AsperGenius multiplex qPCR assay, we did not find azole resistance mutations. With this STRAf assay, A. fumigatus from FFPE tissue and serum was successfully genotyped, allowing retrospective examination of A. fumigatus in culture negative patients with IA.